Financial Development and Inequality in the Global Economy. (11th April 2019) - Ehrlich, Maximilian v.; Seidel, Tobias
Abstract: We build a heterogeneous firms model with firm‐specific wages and credit frictions to study the role of financial development for inequality in the global economy. If there are many small (non‐exporting) firms, better access to external funds reduces wage and profit inequality as well as unemployment. In contrast, if there are many large (exporting) firms, financial development might have opposite effects – especially if trade costs are low. In summary, the implications of financial development for inequality depend on the size distribution of firms and on the costs of exporting. Trade liberalization, however, raises inequality unambiguously.